(untitled) (Journal of the College of Basic Education, 2022)
Dwight Eisenhower (1953-1961) is the 34th President of the United States of America, a Republican politician and an American general, and one of the American presidents who reached the highest position due to their military notoriety during World War II (1939-1945). He held the presidency of the country for two consecutive terms from 1953 until 1961. He was commander-in-chief in the United States Army during World War II, and supreme commander of the Allied forces in Europe. He was also responsible for planning and overseeing the invasion of North Africa in 1942-1943 and the successful Allied invasion of France and Germany in the Western Front in 1944-1945, making Eisenhower famous as the general who led the Allied armies in Europe to victory in World War II. In 1951, he became the first Supreme Commander of NATO until he was elected President of the country in 1953 for two consecutive terms. Eisenhower ended the Korean War in 1953 and also opposed the tripartite aggression against Egypt in 1956. The vacuum in the Middle East and standing against the influence of the Soviet Union in the Arab region.